Research on Micro-renewal Design Strategy of MengZhui Bay Block in Chengdu Old City. Issue 6 (June 2020) - Mei, Wu; Shaoying, Zhang
Abstract: With the continuous expansion of the city, the significance of the regional characteristic culture reflected in the traditional streets space has become increasingly prominent for urban space. Therefore, the renovation of traditional residential streets is of great significance in the urban space repair work. This article takes the current challenges of residential streets in the old city as research issues, and through field investigations and case studies, constructs a set of design strategies suitable for the micro-renewal of traditional houses in the old city of Chengdu.